The Improving of Accounting Competency in Islamic Finance of People Affected by Covid-19 - Happy Sista Devy; Muhammad Rizqi Purnama; Evi Nirmala Dewi; Fatima Zahra Fakir (JURNAL PENELITIAN, 2020)
The community dedication aims to provide the increasing knowledge of Micro, Small and Medium Enterprise (MSME) and household along providing the benefits in the form of improving accounting knowledge competence of people affected by covid-19. Accounting is very important to regulate cash flow and determine the amount of zakat maal that must be paid. In addition, the ISAK 35 financial accounting standard could be the reference to the mosques arranging their financial report in order to attract more donors to improve the mosques’ facilities and infrastructures quality. The results illustrate that the community already knows the importance of accounting in family finances, but on the other hand they still do not have a great knowledge of correct accounting records. By this community dedication, assisted people began to know process the simplest accounting recording for the household, to the detailed recording of MSME and mosques. The informant understanding Islamic financial planning is pretty good approved by assisted household who could explain how the process to measure the amount of zakat in household.